ADSORPTION STUDY OF METHYLENE BLUE USING FE3O4 MODIFIED FOODGRADE ALGINATE - Savitri, Salma
Methylene blue is a dye compound that usually used in many industries like textile, paper, rubber, plastic, leather, cosmetics, pharmaceutical and food industries. In waters, the levels of methylene blue obtained are 5-10 mg/L. The impacts resulting from methylene blue waste are very dangerous because they have high toxic effects, cause allergies and skin irritation, and cause gene changes and are carcinogenic. It is necessary to adsorb methylene blue with an adsorbent. The adsorbent was made by synthesize foodgrade alginate-Fe3O4. This research was done by synthesizing foodgrade alginate-Fe3O4 for methylene blue adsorption, characterizing the adsorbent using FTIR spectrophotometry and XRD, and determining the adsorption isotherm. Based on the results of FTIR spectrophotometry, foodgrade alginate-Fe3O4 has successfully prepared, characterized by the stretching vibrations of O-H bonds that appear in the absorption area of 3430 cm-1, C-H group vibrations in the absorption area of 2918 cm-1, vibrations of the C=O group in the absorption area of 1434 cm-1. cm-1, vibration of the -COO- group in the absorption area of 1434 cm-1, vibration of the C-O group in the absorption area of 1063 cm-1, and vibrations in the Fe-O group in the absorption area of 569 cm-1. Based on the results of the XRD spectrophotometer, it was found that the peaks in the magnetite sample were reflections from 220, 311, 400, 511, and 400. The adsorption of methylene blue using foodgrade alginate-Fe3O4 follows the Langmuir adsorption isotherm model, with an adsorption capacity value is 5.755 mg/g and an %adsorption is 11.51%.